1989
DOI: 10.1088/0953-8984/1/44/033
|View full text |Cite
|
Sign up to set email alerts
|

Phonon propagation in liquid4He: the dependence on injected power and pressure

Abstract: The propagation of phonons in liquid 4He is considered as a function of the number of phonons injected, the ambient pressure, the propagation distance and the ambient temperature. It is shown that there are four main groups of behaviour. The first and simplest is at high pressures, P>19 bar, where apart from some phonon-roton scattering near the heater, the propagation is ballistic and independent of distance and temperature for T<0.3 K. the second group is at low pressures and low injected phonon densities, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…of an I.M.S., the elementary excitations are almost only phonons. As the phonon creation and annihilation processes are very rare in helium II at high pressures [15], we conclude that the assumption that helium II (at low temperatures and high pressures) behaves as an ideal fluid is solidly motivated, even when dissipative processes are taken into account.…”
Section: Liquid Helium II As An Ideal Monoatomic Superfluidmentioning
confidence: 87%
See 1 more Smart Citation
“…of an I.M.S., the elementary excitations are almost only phonons. As the phonon creation and annihilation processes are very rare in helium II at high pressures [15], we conclude that the assumption that helium II (at low temperatures and high pressures) behaves as an ideal fluid is solidly motivated, even when dissipative processes are taken into account.…”
Section: Liquid Helium II As An Ideal Monoatomic Superfluidmentioning
confidence: 87%
“…This behaviour agrees with some experiments which evidence that, for low temperatures and high pressures, helium II behaves as a gas of non-interacting quasi-particles. Indeed, in [15] it is shown that for sufficiently high values of pressure the phenomena of phonon creation and destruction are absent and that the phonon propagation is ballistic. Furthermore in [16] it is shown that the mobility of ions in liquid helium II increases as the temperature is lowered.…”
Section: Liquid Helium II As An Ideal Monoatomic Superfluidmentioning
confidence: 99%